Pacing individual strategies for optimal performance - Thompson, Kevin G. 1966- (Human Kinetics, 2014)
Part I explains the biological and psychological underpinnings of pacing science, including the six commonly used pacing strategies that are discussed in detail throughout the book: all-out, positive, even, negative, parabolic and variable. Part II shows how to apply the science, offering pacing recommendations and considerations for time-dependent sports such as running, triathlon and swimming and exploring the role of pacing in racket sports and several team sports. Combining scientific research and real-world profiles of elite athletes and coaches, Pacing: Individual Strategies for Optimal Performance shows coaches and athletes how to develop the ideal pacing plan for every competition. -- from back cover